Recording Maybe? Location-Based Application for Detection and Capture of Ad-hoc Meetings - Viel, Caio C.; Zimmermann, Larissa C.; Rodrigues, Kamila R.H.; Pimentel, Maria G.C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
University campi, start-ups and conferences venue are places where there is a constant flow information exchanged between individuals. Part of this exchange takes place in formal, scheduled meetings, presentations, lectures and workshops. Another part, however, occurs in ad-hoc encounters such as coffee breaks, or when we meet colleagues or supervisors in corridors or at the canteen. Some have the habit of recording the information and decisions from formal encounters by taking notes on paper or capturing audio or video. However, this is not always possible in ad-hoc meetings, either because of lack of means to carry out the notes or because participants do not realize the need to record what was discussed, thus many information and decisions taken in ad-hoc meetings are lost. In this paper we present a case study that investigates how common is the occurrence of ad-hoc meetings in university campi, and proposes the "Context-Based Opportunistic Capture", a Capture & Access technique that uses mobile devices to detect possible occurrences of meetings from user's close proximity and alerts them that a meeting may be held, and suggests that they use their devices to record the meeting in audio or video. As proof of concept we developed an Android application and a context server that were evaluated by means of a case study. Partial results indicate that ad-hoc meetings are indeed common, that these are not usually recorded and that the provision of an infrastructure for the capture and registration of these meetings proves feasible, especially for the aforementioned environments.